2017
DOI: 10.18524/1810-4215.2017.30.114129
|View full text |Cite
|
Sign up to set email alerts
|

The Abc of Cosmography

Abstract: ABSTRACT. The basis of this work is the scheme for describing the universe, called the "cosmography" entirely based on the cosmological principle. Within the framework of such a scheme the parameters of any model that satisfies the cosmological principle (the universe is homogeneous and isotropic on large scale), can be expressed through cosmographic parameters. We demonstrate a number of advantages of the approach used before traditional methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Applying the field equations of the first case for the three different values of β and for w = 1, −1, 1 3 and w = 0, revealed that the relationships between the values of β and the types of future singularities were the same as those under the FRW gravity (Figs. 3,4,5,6,7,8). In the case f = R + αRR µν T µν , however, the study of field equations and the singularities which might happen in the future of the universe unfolded interesting result.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the field equations of the first case for the three different values of β and for w = 1, −1, 1 3 and w = 0, revealed that the relationships between the values of β and the types of future singularities were the same as those under the FRW gravity (Figs. 3,4,5,6,7,8). In the case f = R + αRR µν T µν , however, the study of field equations and the singularities which might happen in the future of the universe unfolded interesting result.…”
Section: Discussionmentioning
confidence: 99%
“…The H, q, j, s are kinematical quantities, which are directly extracted from the spacetime. The kinematic quantities are defined as [56,57]…”
Section: Cosmographic Parametersmentioning
confidence: 99%
“…Under the background of the homogeneous and isotropic universe characterized by the FLRW universe, one can define the kinematical quantities as [54,55]…”
Section: Evolution Of the Cosmographic Parametersmentioning
confidence: 99%